Efficient DSP Receiver Architecture for Underwater Acoustic Communications (Al-Mansour Journal, 2022)
In this paper, design of coherent receiver for underwater acoustic communication applicable for digital signal processor (DSP) is presented. This includes the use of channel coding in the form of bit-interleaved coded modulation with iterative decoding(BICM-ID). An architecture of single carrier receiver is suggested instead of multicarrier modulation to be implemented for real-time applications. To investigate the architecture, simulation results obtained by MATLAB are presented and reveal that BICM-ID is useful to mitigate errors through AWGN channel. Additionally, we adopt C language to investigate the receiver architecture that can be applied for realtime applications
Keywords: BICM-ID; DSP; UNDERWATER ACOUSTIC